Effect of gender on the vibration transmissibility ratio from different operations of angle grinder - Eng, Jia-Jun; Teoh, Choe-Yung; Goh, Yeh-Huann; Tan, Wei-Hong (AIP conference proceedings, 2023)
The repeated exposure to high levels of vibration from power tools is known to cause injury to workers over time. However, studies investigating the vibration transmission from power tools have used either mixed-gender subjects or male subjects. No study has investigated the effect of gender on the vibration transmissibility ratio during operation of angle grinder. The objective of this study is to investigate the effect of gender on vibration transmissibility ratio from different operations of angle grinder. In this study, a total of 14 subjects (seven males and seven females) were exposed to hand-arm vibration from grinding and cutting operations of angle grinder. The experimental vibration analysis was carried out using LMS SCADAS Mobile with post-processing software LMS Test Lab. The results showed that the vibration transmissibility ratio was higher on female subjects than male subjects for both grinding and cutting operations. The results were then interpreted to maximum allowable safety time according to ISO 5349. The results showed that the maximum allowable safety time for male subjects were 6.64 hours and 7.23 hours respectively for grinding and cutting operations, while the maximum allowable safety time for female subjects were 6.21 hours and 6.67 hours respectively. The results of this study imply the need for gender-specific maximum allowable safety time.